MATHEMATICAL COMPUTATION OF NEURONAL TRANSMISSION OF INFORMATION - Krishnan, V. (International Journal of Psychosocial Rehabilitation, 2020)
This study will attempt to put forward a mathematical model asymmetric to the significance of the neurons in data transmission. The mathematical perspective should endorse the neuronal transmission assuming a basic job in forming synaptic quality and networking at all phases of neuronal turn of events and capacity. The study is significant considering the fact that a neuron responds to changes in synaptic transmission by tweaking quality articulation programs, which manage significant synaptic elements. In this manner, it isn't astounding that neuronal action profoundly affects all parts of mi-RNA biogenesis and capacity, thus forming the basis of human life.